Team Building PKE 2024: words of thanks from KPP / PM. Ir. Dr. Nor Azlan Othman, Wan Salha Saidon and Norsabrina Sihab - Othman, Nor Azlan; Saidon, Wan Salha; Sihab, Norsabrina (PKE, UiTMCPP, 2024)
I would like to extend my heartfelt gratitude to everyone who participated in and contributed to the success of our recent team building (TBPKE2024) event held on the 6th and 7th of July 2024. The two days and one night spent together were filled with adventure, laughter, memorable activities, and camaraderie. From hiking over 3km through the lush jungle, tubing down a thrilling 1km stretch of river, to conquering the tree top walk, every moment was packed with excitement. The final event, a delightful barbecue by the river featuring marinated lamb and chicken, was the perfect conclusion to our outdoor experiences. Our tasks during the activities, especially creating those short videos, brought out the creativity and spirit of competition in all of us.